Impact of Digitalization and Renewable Energy on Environmental Quality in Pakistan (Journal of Asian Development Studies, 2026)
This study examines how digitalization and renewable energy affect environmental quality in Pakistan, using time series data from 1996 to 2023. It uses robust econometric techniques: the Augmented Dickey-Fuller (ADF) unit root test, ARDL bounds testing, and short-and long-run ARDL models. The unit root testfound a mix of I(0) and I(1) variables, making ARDL appropriate. The ARDL bounds test confirmed a long-run cointegration between environmental quality and the chosen variables. ARDL long-run estimates indicate that renewable energy and digitalization are negatively and significantly associated with environmental degradation. In contrast, industrialization and population growth are positively linked to environmental degradation. These results reveal the potential for digital and clean energy technologies todrive sustainable development and highlight the need to green the industrial sector and align financial systems with environmental goals.